SOUTH MORAVIAN BANK ‒ NIŠ (1894 - 1929) (Heritage, 2022)
At the end of the 19th century, a large number of local banks were established on a sheregolder basis in the Kingdom of Serbia. Among them was the Niš Cooperative for Credit and Savings. Apart from banking, this institution was also engaged in industrial affairs and was the owner of a brick faktory. From 1910, the name of the institution was the Niš Credit Bureau, which operated succsessfully until the outbreak of the Great War.After the end of the war, the bank changed its name again and was called the South Moravian Bank. In order to continue its operations, the Bank recapitalized and the majority owners became shareholders from Belgrade. Within her company, she also had a commodity department and was engaged in trade. Non-banking operations were dominant, which brought the bank into an unfavorable situation with the change of business conditions in the Kingdom of Serbs, Croats and Slovenes. There were losses due to this type of business, but also because they could not quickly collect receivables from the state, especially from the municipality of Niš.The liquidation that was initiated in 1927 was caused by the losses of the goods department, but also by constant misunderstandings between the shareholders from Niš and Belgrade. Even joint decisions were not implemented, so the shareholders from Niš concluded that further joint work is impossible. That is why they wanted either they to continue working or shareholders from Belgrade. Disagreements between the members of the management and the Liquidation Board did not give a chance for the South Moravian Bank to get out of the problem, so by the end of 1929 it was shut down.
Keywords: Niš Cooperative for Credit and Savings, Niš Credit Bureau, South Moravian Bank, brick faktory,commodity departement, liquidation